Enterprise Informality in India: The Blind Spots in Public Policy - Santosh Mehrotra; Tuhinsubhra Giri (The Indian Journal of Labour Economics, 2023)
An essential characteristic of firm size distribution patterns in developing countries including India, is a bimodal distribution with a "missing middle", which is widely accepted in development economics. We analyse data from the Annual Survey of Industries (ASI), National Sample Survey (NSS)~and Economic Census to assess the firm~size structure of the whole non-farm sector. The contribution of the paper is that for the first time a comprehensive database is constructed to enable analysis of the size structure of India's non-farm enterprises. The second contribution is that we find a deep distortion in India, with even a "small"-scale sector being very small, relatively. We examine briefly the policy-related causes that make India an outlier even among Asian economies in respect of size structure of enterprises. Finally, we argue that the historically policy-induced informality of enterprises is being entrenched by the current hiatus in state policy in even recognising the true nature of the problem of micro, small & medium enterprises (MSMEs), which holds back both their~growth and employment.
Keywords: 330; Size distribution of firms; Firm performance: size; Diversification; Scope; Enterprise policy; Formal and informal sectors